Nilai-Nilai Pendidikan Berwawasan Gender Dalam Buku Ajar PAI dan Budi Pekerti Kelas XII SMA - Salamudin, Ceceng; Sidiq, Haryadi Purnama (STAI Al-Musaddadiyah Garut, 2025)
This research focuses on analyzing gender-oriented educational values ​​in Islamic Religious Education and Characteristics class 12 high school textbooks. Gender equality is an important issue that continues to be fought for, including in the context of education in Indonesia. Textbooks have a crucial role in shaping students' views and thinking patterns, so fair and equal representation is very necessary. This research aims to identify and evaluate the representation of gender equality and inequality values ​​in the textbook. The research method used is literature with a content analysis approach, which includes analysis of text illustrations, images, and material studies. This analysis was carried out to see the extent to which PAI and Budi Pekerti textbooks reflect the principles of gender equality. The results of the research show that male images and figures are more dominant than female in the textbook, even though several values ​​of gender equality are reflected. This gender inequality is seen in the use of models in inspirational texts and depictions of occupational fields, where men are more often represented in important or leadership roles. This research is expected to provide deeper insight into the integration and interpretation of gender values ​​in PAI and Budi Pekerti textbooks. It is hoped that these findings will encourage the revision of textbooks that are more balanced and responsive to gender equality issues, so that they can make a positive contribution to efforts to build a generation that is more aware and sensitive to the importance of gender equality. Keywords: gender insight education, character and islamic religious education textbook